Numerical Analysis of FLiBe Laminar Convective Heat Transfer Characteristics in Tubes Fitted With Coaxial Cross Twisted Tape Inserts - Yang, Zimu; Liu, Xiaoya; Cao, Xiaxin; Gao, Zhichao; Ding, Ming (Frontiers in Energy Research, 2020)
Molten salts are now widely used as heat transfer fluids in solar thermal plants and molten salt nuclear reactors. In order to explore their heat transfer enhancement method, new coaxial cross twisted tapes (CCTTs) are applied to plain tubes with molten salt FLiBe as the working fluid, and the characteristics of pressure drop and heat transfer are numerically investigated by the CFD software STAR-CCM+. Simulations are performed in a laminar flow regime where the Reynolds number ranges from 100 to 1100, and the velocity, temperature profiles, and enhanced performance evaluation criteria (PEC) are analyzed to investigate the heat transfer performance of FLiBe in the tube fitted with CCTTs and typical twisted tape (TT). Research was performed on water and lubricating oil to investigate the effects of fluid thermal-physical properties on the performance of CCTTs. The results show that CCTTs can produce stronger swirl flow and greatly enhance heat transfer. For overall heat transfer performance, the maximum PEC of FLiBe with CCTTs reaches 2.37. The comparison of three different fluids also indicates that CCTTs have better heat transfer performance for higher Prandtl number fluids such as molten salt. The correlations of CCTTs and TT are developed into a unified form for the prediction of friction factors and Nusselt numbers for various Prandtl number fluids.